Asian J Biomed Pharmaceut Sci 2019
DOI: 10.35841/2249-622x.67.19-066
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of doctors working at Upazila Health Complexes in Barisal District.

Abstract: Doctor's profession has long been among one of the most attractive professions in our society, but doctors are increasingly getting dissatisfied with their jobs. Job satisfaction is very important but very less studied issue. The aim of this study to assess the level of job satisfaction among doctors at selected Upazila Health Complexes in Barisal District. A descriptive cross sectional study was conducted among 59 doctors posted in 9 Upazila Health Complexes of Barisal district. Data was collected by using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Observations indicate that a lack of job satisfaction among physicians and low retention of qualified workforce are among the top contributing factors to the poor quality of services. Rashid et al [41] found that the level of job satisfaction among physicians at the UHCs is very low. They identified multiple factors that contribute to this dissatisfaction, which include low salary, limited scope for promotion, poor service allowances, mandatory night shift duty, long working hours, and lack of accommodation and transportation facility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations indicate that a lack of job satisfaction among physicians and low retention of qualified workforce are among the top contributing factors to the poor quality of services. Rashid et al [41] found that the level of job satisfaction among physicians at the UHCs is very low. They identified multiple factors that contribute to this dissatisfaction, which include low salary, limited scope for promotion, poor service allowances, mandatory night shift duty, long working hours, and lack of accommodation and transportation facility.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the quality of healthcare services at UHCs, most of the previous studies looked at access to healthcare, [43,44] patients' satisfaction, [31] physicians' job satisfaction, [41] and retention of the healthcare workforce. [45] Although it is well established that good patient outcomes are strongly correlated with physicians' good clinical judgment, little is known about physicians' decision-making and influencing factors in the context of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%